Research Progress on the Impact of Traditional Chinese Medicine Treatment on Tumor Microenvironment - Jiang, Bin; Wang, Zhen; Yuan, Jia; Quan, Jianfeng (Journal of Contemporary Medical Practice, 2024)
Tumor microenvironment mainly includes non-tumor cells, cytokines, chemokines and extracellular matrix. It is an important part of anti-tumor immunity and plays a vital role in the formation and invasion of tumors. Anti-tumor treatment is in line with the concept of "Fuzheng anti-cancer" of traditional Chinese medicine, and the regulation of anti-tumor traditional Chinese medicine on the tumor microenvironment can be expounded based on the body's immunomodulation mechanism. It discusses strengthening the body's immune barrier, curbing tumor growth from the source, and reversing the microenvironment that is conducive to tumor survival; it can guide the normalization of tumor blood vessels to reduce the probability of tumor infiltration, metastasis and recurrence; and improve the quality of life of the host by reducing adverse reactions caused by therapeutic drugs.